Analysis of Excellent Academic Service in Increasing Student Satisfaction at SMK Karya Guna 1 Bekasi - Muslim, Aziz; Muthi, Ibnu; Baharuddin (Proceeding International Conference on Education, 2023)
This research was motivated by the low performance of academic services in an educational institution. The research uses qualitative with a phenomenological approach. The data sources are principals, teachers. Staff and learners. Research shows that the Academic Administration Service of SMK Karya Guna 1 Bekasi Teachers of SMK Karya Guna 1 Bekasi have the competence to create a pleasant learning atmosphere so that the material taught can be understood by students well.  All satisfaction with students has been achieved, by providing quality services characterized by the comfort of students in receiving academic services provided by SMK Karya Guna 1 Bekasi and school fees that are implemented into values (benefits) that are in accordance with student expectations. The strategy to improve the quality of academic services at SMK Karya Guna 1 Bekasi by increasing the satisfaction of students in the quality of service is evidenced by the adjustments in the field including the suitability of the curriculum between expectations and reality, the suitability of learning infrastructure between expectations and reality, the suitability of learning implementation between expectations and reality, the suitability of academic assistance between expectations and reality.